Diffusion properties of electrons in GaN crystals subjected to electric and magnetic fields - Syngaivska, G.I.; Koroteev, V.V.; Kochelap, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
We have studied the diffusion coefficient of hot electrons in GaN crystals under moderate electric (1...10 kV/cm) and magnetic (1…4 T) fields. Two configurations, parallel and crossed fields, have been analyzed. The study was carried out for compensated bulk-like GaN samples for various lattice temperatures (30…300 K) and impurity concentrations (10¹⁶…10¹⁷ cm⁻³). We found that at low lattice temperatures and low impurity concentrations, electric-field dependences of the transversal-to-current components of the diffusion tensor are non-monotonic for both configurations, while diffusion processes are mainly controlled by the magnetic field. With increasing the lattice temperature or impurity concentration, the behaviour of the diffusion tensor becomes more monotonous and less affected by the magnetic field. We showed that this behaviour of the diffusion processes is caused by the distinct kinetics of hot electrons in polar semiconductors with strong electron – optical phonon coupling. We have suggested that measurements of the diffusion coefficient of electrons subjected to electric and magnetic fields facilitate the identification of features of different electron transport regimes and the development of more efficient devices and practical applications.